Weyl-van der Waerden spinor technique for spin-3/2 fermions - Novaes, Sérgio Ferraz [UNESP]; Spehler, D. [UNESP] (Elsevier B.V., 1992)
We use the Weyl-van der Waerden spinor technique to construct helicity wave functions for massless and massive spin-3/2 fermions. We apply our formalism to evaluate helicity amplitudes taking into account some phenomenological couplings involving these particles.